Perception of women in chemical dependency situation inside Mato Grosso, Brazil - Vagner Ferreira do Nascimento; Marciana Fernandes Moll; Alisséia Guimarães Lemes; Juliana Fernandes Cabral; Tayane Próspero Cardoso; Margarita Antonia Villar Luis (Universidad de Alicante, 2017)
This study aimed to know the perception of women in chemical dependency situation within Mato Grosso. This is a descriptive and exploratory qualitative study, based on the theory of Peplau. Held in the only female therapeutic community, belonging to the Northeast of Mato Grosso - Brazil, in the period March-April 2016, with 15 women. Data collection occurred in the service itself, using semistructured interviews with writing and recording. For analysis, we used the Content Analysis. The results revealed that women in treatment in this community have similar drug-related experiences but tend to respond differently to treatment, especially since not all women have chemical dependency as their primary reason for being in that care facility. It 2º Cuatrimestre 2017 • Año XXI - N.° 48 Cultura de los Cuidados 34 is concluded that the therapeutic communities should strive to recognize the weaknesses presented by the women since the reception to develop therapeutic plans based on the potential of women. To do so, these services must value the multiple needs of these women, so that by providing them, greater possibilities of recovery can be made possible.